Attitudes towards statistics in economic and administrative sciences: An analysis by undergraduate stage - Torres Ceballos, Carlos Gerardo (2020)
The purpose of this research was to: 1) characterize attitudes towards statistics in the initial, intermediate and final stages of undergraduate degrees in Administrative Economic Sciences and, 2) determine the applications that students give to statistics during their university studies. 159 students (69.18% female and 30.81% male) participated in careers such as Human Resources, Administration, International Business and Marketing, which answered a semantic differential questionnaire composed of seven pairs of extreme adjectives based on a scale of -3 to + 3. The results showed that, during the three stages of the races (initial, intermediate and final), the attitudes towards statistics remain somewhat positive (with averages of 0.73, 0.94 and 1.00, respectively) and that, although their importance is perceived, they are somewhat tense for students. It was also found that these attitudes are used to understand information, calculate data and investigate. In addition, possible explanations for such findings are discussed, for example, the teaching strategies of teachers and the academic history of students.